(untitled) (Research, Society and Development, 2023)
The crisis generated by the pandemic impacted several factors in people’s daily lives and promoted changes that led to increased stress. This situation draws attention to possible psychiatric complications, not only in patients who have already been infected by the virus, but also in the entire population who had to deal with the measures implemented by the government. Thus, this study is based on evaluating the population’s immune compromise associated with stress conditions in the face of the COVID-19 pandemic. This is an integrative literature review, with a qualitative approach based on the collection of national and international data from the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Scientific Electronic Library Online (SciELO) and Google Scholar. In the study, the relationship between the nervous, immune and endocrine systems was observed, altering mechanisms in the neuroendocrine immune circuits and causing damage to health due to the stress processes of social isolation. There was increased expression of pro-inflammatory genes and decreased expression of antiviral genes, increasing the risk of complications from COVID-19 due to changes in cytokine transmission. Stress and COVID-19 increase the secretion of IL-6, a cytokine that is associated with death in cases of COVID-19. In health professionals there were changes in immune cells after being exposed to stressors. In view of the results obtained, it was found that stress during the pandemic affected the immune system by altering the response against SARS-CoV-2, increasing viral pathogenesis.